Further applications of magnetic resonance - Hayes, W (1959)
The electron and nuclear magnetic resonance techniques are now well established and are extensively applied to the investigation of the solid state. We are at present largely concerned with the investigation of defect sites in ionic crystals which are associated with unpaired electronic spins. Phosphor and semiconductor physics are concerned in many instances with the behaviour of an impurity ion in a host lattice. An impurity cation will, in general, enter a host lattice substitutionally and in some cases may cause distortion of the lattice. Charge compensation must occur when the charge on the impurity cation and the host cation are not the same and the mechanics by which this is achieved is of interest. Accurate information about the behaviour of paramagnetic impurities may be obtained from the resonance spectrum. Many irradiation induced defects in alkali halides are paramagnetic and may be investigated by the electron resonance technique; addition of impurities extends the range of irradiation induced defects which may be produced. The stability of irradiation centres is temperature dependent and the variety of centres is enhanced by irradiation at low temperature. The nuclear magnetic resonance technique may be used to determine non-nuclear properties of materials. We are concerned here with magnetic interactions in paramagnetic iron group fluorides using the fluorine nucleus as a probe. The techniques which have been used to detect electron and nuclear magnetic resonance are outlined. RESULTS Iron Group Impurities in NaF Crystals of NaF ware grown containing chromium, manganese, iron, cobalt or nickel ions. The paramagnetic resonance spectra of Mn2+ and Co2+ ions were observed. The divalent ions replace Na+ ions and are presumably accompanied by positive ion vacancies to balance the excess charge. Four different types of Mn2+ spectrum are observed with D values of 89, 225, 325 and 380 × 10-4 cm-1. The non cubic symmetry arises from association with positive ion vacancies; the variation in D arises from variation in the degree of association. The Co2+ spectrum, has rhombic symmetry. The failure to observe the non-Kramers ions Cr2+, Fe2+ and Ni2+ nay be due to the reduced symmetry produced by a vacancy. The ions Cr+, Fe+, Co+ and Ni+ are observed in cubic surroundings after X, γ or electron irradiation at room temperature and the resonance spectra have properties which are familiar from previous investigations of the corresponding isoelectronic divalent ions. It appears that divalent iron group ions are effective electron traps at room temperature in NaF. The electron deficient centres which are the source of the trapped electrons have not been determined. The monovalent ions are annealed out by heating to about 140°C and the original state of the crystal is restored. Most of the spectra investigated show a resolved fluorine structure due to weak covalent bonding of the magnetic electrons with the surrounding fluorine ions. Analysis of this structure gives information about the environment of the impurity ion and indicates that the magnetic electrons spend about 2 of the time in n = 2 orbitals on each of the nearest neighbour fluorine ions. Nuclear Magnetic Resonance in FeF2 and CoF2 The paramagnetic ions of FeF2 and CoF2 acquire a considerable mean magnetisation in an external magnetic field end it is expected that the time averaged dipolar field of the magnetic ions at the fluorine nuclear positions will displace the fluorine nuclear magnetic resonance line by several gauss from its normal value of ω/γN. Measurements made at 30 mcs show however that in addition to the expected anisotropic dipolar shift, an extremely large isotropic shift occurs; this shift has the same temperature dependence as the bulk paramagnetism and in the ease of FeF2 at 195°K is 5% of the applied magnetic field while in the ease of CoF2 at 90°K a fractional shift of 8% is found. The large internal fields at the fluorine nuclei responsible for this shift are produced by the weak covalency of the Fe2+ and Co2+ - F- bond. It may be shown that at a frequency v, the fluorine magnetic resonance line will occur at magnetic fields given by hv = gNβN H (1 + α) where βN is the nuclear magneton, gN is th« fluorine nuclear g-factor and the fractional field shift is α where α = 1337χ⁄g ΣN AN if A is in units of cm-1; here χ is the molar susceptibility, g is the electronic g-factor and AN is the h.f.s. constant for the interaction between the fluorine nucleus and the Nth paramagnetic ion. Values of g and AN are available from electronic ascetic resonance measurements on Fe2+ and Co2+ ions present as trace impurities in ZnF2 and we may compare calculated values of α with the measured values. In the case of FeF2 the measured values of α are a few per cent larger than the calculated values but with CoF2 the agreement is very poor; this is not unexpected since the expression for α was derived assuming 'spin-only' magnetism and this condition does not hold in the case of CoF2. Paramagnetic Impurities in CaF2 Rare earth impurities were introduced into the cubic CaF2 lattice and the paramagnetic resonance spectra of Ce3+, Eu2+, Gd3+ and Er3+ ions were observed. The trivalent ions replace Ca2+ ions and charge compensation is generally achieved by the introduction of an F- ion into the nearest interstitial site; this introduces tetragonal symmetry about a cube edge into the crystal field at the impurity ion and there are three distinguishable centres with similar spectra in the magnetic unit cell. The g-values of Ce3+ are g″ = 3.038 ± 0.003, g⊥ = 1.396 ± 0.002. Transitions within two doublets of Er3+ in a tetragonal field were observed with (a) g″ = 7.76 ± 0.02, g⊥ = 6.253 ± 0.006, (b) g″ = 6.76 ± 0.02, g⊥ = 9.11 ± 0.01; the doublet which gives rise to (b) is about 36k above the ground doublet which gives rise to (a). Er3+ ions also occur in a cubic field with g = 6.78 ± 0.01; in this case the cubic symmetry is not reduced presumably because of remote charge compensation. A complete analysis of the Gd3+ spectrum was not possible because of the large overall zero field splitting (~ 2 cm-1) of the ground octuplet which is largely due to the tetragonal field. The cubic crystal symmetry is maintained in the ease of Eu2+ and the constants of the spectral are g = 1.989 ± 0.002, 151A = 34.5 ± 0.2 × 10-4 cm-1, 153A = 15.3 ± 0.4 × 10-4 cm-1; the overall zero field splitting of the octuplet is 0.186 cm-1. Iron group ions were also introduced into the CaF2 lattice. Mn2+ ions are present with cubic symmetry and a complete analysis of the spectrum shows that the cubic field splitting is small (a = + 0*6 ± 0.4 × 10-4 cm-1) Spectra hare also been observed which have been assisted to Cr2+ and Co2+ ions but a local distortion of the lattice makes the interpretation of the spectra difficult. The iron group ions show a resolved fluorine structure characteristic of weak covalent bonding with nearest fluorines bat this it not evident with rare earth ions because the magnetic electrons are more localised. In the ease of the rare earths, a fluorine satellite structure is observed due to the simultaneous flipping of the electron spin and the nuclear spin of a nearest fluorine ion; this effect arises from a weak magnetic coupling, partly dipolar in origin, between the electron spin and the nuclear spin. V-centres in Alkali Halides Crystals of KCl and KBr containing Ba2+, Sr2+ or Ca2+ ions were X-irradiated at 195°K and the paramagnetic resonance spectra investigated without warming the crystals. Spectra were observed which have been assigned to Cl2- and Br2- molecule ions (these centres are described as V-centres, hole centres or electron deficient centres) alined approximately along a cube edge. The electrons released by the irradiation are trapped as F-centres. These results are in contrast with measurements on pure crystals or crystals containing good electron traps such as silver, thallium or lead where Cl2- and Br2- centres are observed alined accurately along a face diagonal. It is proposed that the approximate cube edge aliment arises from the trapping of the V-centres at positive ion vacancies associated with the divalent impurity ions. The spectra may be approximately fitted to the spin Hamiltonian ℋ = g″βHzSz + g⊥β (HxSx + HySy) + AIzSz + B(IxSx + IySy) where S = 1⁄2 and I = I1 + I2 where I1 = I2 = 3⁄2 is the spin of the halogen nuclei. There are three resolved Cl2- isotopic species, 35-35, 35-37, 37-37; the Br2- isotopic species 79-79, 79-81 and 81-81 are also resolved. The constants of the spectrum of Cl2- (35-35) are g″ = 2.005 ± 0.003, g⊥ = 2.04 ± 0.01, A = 89.0 × 10-4 cm-1, B = 13 × 10-4 cm-1. The only measurable constants of Br2- (81-81) are g″ = 1.991 ± 0.003 and A = 419 × 10-4 cm-1. Potassium Chloride Containing Silver When crystale of KCl containing Ag+ ions are X-irradiated at 77°K, Cl2- ions alined along a crystal face diagonal are rapidly produced because Ag+ ions are efficient electron traps. A Ag+ ion which traps an electron becomes a neutral paramagnetic silver atom (Ag°). The resonance spectra of both Cl2- and Ag° have been observed, the latter showing a resolved chlorine structure. Silver has two isotopes, and 109Ag each with I = 1⁄2. The constants of the spectrum of 109Ag are g = 1.997 ± 0.003, A = 620 ± 2 ×10-4 cm-1. When the crystals are warned to 208°K a luminescent glow is observed and the spectrum change*, the Cl2- centres disappear, the Ag° concentration is reduced by about 20 and a new paramagnetic hole centre is produced. The bole is localised mostly on a silver ion and two chlorine ions (for this reason we refer to the centre as AgCl2) and within the accuracy of measurement has axial symmetry about a cube edge; there are three distinguishable centres in the magnetic unit cell, each with similar spectra. The spectrum any be fitted to the spin Hamiltonian ℋ = g″βHzSz + g⊥β (HxSx + HySy) + AIzSz + B(IxSx + IySy) + A″[(IozI + IozII)Sz] + B″[(IoxI + IoxII)Sx + (IoyI + IoyII)Sy] where S = 1⁄2, I = 1⁄2 is the spin of the silver nucleus, IoI = IoII = 3⁄2 is the spin of the chlorine nucleus, g″ = 2.196 ± 0.006, g⊥ = 2.058 ± 0.005, A = 38 ± 2 × 10-4 cm-1, B = 30 ± 4 × 10-4 cm-1 A″ < 4 × 10-4 cm-1 and B″ = 30 ± 4 × 10-4 cm-1. On heating to 373°K, electrons are released from Ag° centres forming Ag+ ions and are captured by the AgCl2 hole centres with the emission of a luminescent glow; the AgCl2 centres are destroyed and the crystal is restored to its condition before irradiation.